Exploration of Gastronomic History and Culinary Potential of Bitung City as a Tourism Attraction - Mantiri, Maurits (Universitas Syiah Kuala, 2024)
Bitung City in North Sulawesi has a rich history and culinary culture that is interesting to be explored as a tourist attraction. This research aims to explore the gastronomic history and culinary potential of Bitung City through a literature study approach. The method used was qualitative research by conducting a literature review of various relevant sources such as books, journal articles, and historical documents. The results of the study show that Bitung City has a distinctive culinary heritage, rooted in a combination of local and external cultural influences such as Europe and China due to the history of trade in the region. Typical foods such as Shasibi made from raw tuna fish reflect Bitung's characteristics as a coastal city. There are also a variety of other cuisines with local ingredients and distinctive traditional cooking techniques. Bitung's rich gastronomic history and culinary uniqueness have great potential to be developed as a tourist attraction that attracts tourists, while preserving culinary culture as a regional identity. Synergy is needed from the government, industry players, and the community in introducing and promoting Bitung culinary. This research concludes the importance of in-depth exploration of gastronomic history and the development of culinary tourism based on regional local wealth.